Phylogenetic analysis of two Ukrainian isolates of Wheat streak mosaic virus - Mishchenko, L.T.; Dunich, A.A.; Skrypkina, I.Ya.; Kozub, N.O. (Вiopolymers and Cell, 2019)
The study of molecular characteristics and, in particular, the nucleotide (nt) and amino acid (aa) sequences of the viral genomes, is necessary to know the changes in their geographical range, phylogenetic relationships, viruses’ evolution, and their emergence as new epidemics. Aim. Phylogenetic analysis of the coat protein (CP) gene sequences of two new Ukrainian isolates of Wheat streak mosaic virus: Ukraine-Mal-18 and Ukraine-Ep-18. Results. The nucleotide sequences of 676 nt region of the CP gene of two Ukrainian WSMV isolates were compared with the sequences of 72 WSMV isolates/strains from GenBank. The phylogenetic analysis showed that the Ukrainian WSMV isolates cluster with the clade B or WSMV-ΔE isolates (originating from Europe and Asia) and have a typical for this clade triplet deletion at the position 8412-8414 nt in the CP gene. The isolate Ukraine-Mal-18 has the highest level of the sequence identity (93.5%-95.9% nt and 93.6-95.0% aa) with the clade B isolates. The Ukraine-Ep-18 isolate shares 89.2%-91.4% (nt) and 88.6-87.1% (aa) identity with the clade B isolates. Additionally, both Ukrainian WSMV isolates have a number of unique aa substitutions in the central CP gene domain. Conclusions. Ukrainian WSMV isolates belong to the clade B. But Ukraine-Mal-18 and Ukraine-Ep-18 have some differences from other members of the clade: i) a higher divergence compared to other B isolates (the Ukraine-Mal-18 has 12 aa substitutions, the Ukraine-Ep-18 has 25 aa substitutions, whereas the other clade B isolates have no more than 2 aa substitutions); ii) have aa substitution identical with the B1 non-crop isolates of this virus, many aa substitutions are in the same motifs as the substitutions of B1 grass WSMV isolates. Дослідження молекулярних характеристик, зокрема, нуклеотидних (нт) та амінокислотних (аа) послідовностей вірусних геномів, є необхідним для з’ясування змін у географічному ареалі, філогенетичних зв’язків, еволюції вірусів та їх появи у вигляді епідемій. Мета. Філогенетичний аналіз гену капсидного білка (СР) двох нових українських ізолятів вірусу смугастої мозаїки пшениці (ВСМП) Ukraine-Mal-18 та Ukraine-Ep-18. Методи: імуноферментий аналіз, виділення тотальної РНК із рослинного матеріалу, полімеразна ланцюгова реакція зі зворотною транскрипцією, сиквенування, філогенетичний аналіз. Результати. Послідовності гену СР розміром 676 нт двох українських ізолятів ВСМП порівнювали із послідовностями 72 ВСМП ізолятів/штамів із бази даних GenBank. Філогенетичний аналіз показав, що українські ізоляти входять до клади В або WSMV-ΔE (походять із Європи та Азії) та мають типову для цієї клади делецію триплету у позиціях 8412-8414 нт у гені СР. Ukraine-Mal-18 має найвищий відсоток ідентичності за нуклеотидною послідовністю 93,5%-95,9%, за амінокислотною – 93,6-95,0% із ізолятами клади В. Ізолят Ukraine-Ep-18 із ізолятами клади В має ідентичність 89,2-91,4% (нт) та 88,6%- 87,1% (аа). Крім того, у двох українських ізолятів відмічено низку унікальних аа заміщень в центральній ділянці гену СР. Висновки. Українські ВСМП ізоляти входять до клади В. Але Ukraine-Mal-18 та Ukraine-Ep-18 мають деякі відмінності від них: і) вищу дивергенцію, ніж інші ізоляти групи В (Ukraine-Mal-18 має 12 аа заміщень, Ukraine-Ep-18 має 25 аа заміщень, а інші ізоляти клади В мають 0-2 аа заміщення); іі) мають аа заміщення, ідентичні із непшеничними ізолятами групи В1 цього вірусу, багато аа заміщень знаходяться в тих самих ділянках гену СР, що і заміщення трав’яних В1 ізолятів ВСМП. Исследование молекулярных характеристик, в частности, нуклеотидных (нт) и аминокислотных (аа) последовательностей вирусных геномов, необходимо для выяснения изменений географическогоареала, филогенетических связей, эволюции вирусов и их появления в виде эпидемий. Цель. Филогенетический анализ гена капсидного белка (СР) двух новых украинских изолятов вируса полосатой мозаики пшеницы (ВПМП) Ukraine-Mal-18 и Ukraine-Ep-18. Методы. Иммуноферментный анализ, выделение тотальной РНК из растительного материала, полимеразная цепная реакция с обратной транскрипцией, сиквенирование, филогенетический анализ. Результаты. Последовательности гена СР размером 676 нт двух украинских изолятов ВПМП сравнивали с последовательностями 72 ВПМП изолятов / штаммов из базы данных GenBank. Филогенетический анализ показал, что украинские изоляты входят в кладу В или WSMV-ΔE (происходят из Европы и Азии) и имеют типичную для этой клады делецию триплета в позициях 8412-8414 нт в гене СР. Ukraine-Mal-18 имеет наиболее высокий процент идентичности по нуклеотидной последовательности 93,5%-95,9% и аминокислотной – 93,6-95,0% с изолятами клады В. Изолят Ukraine-Ep-18 с изолятами клады B имеет идентичность 89,2-91,4 % (нт) и 88,6% - 87,1% (аа). Кроме того, у двух украинских изолятов отмечен ряд уникальных аа замен в центральном участке гена СР. Выводы. Украинские ВПМП изоляты входят в кладу В. Но Ukraine-Mal-18 и Ukraine-Ep-18 имеют некоторые отличия от них: i) выше дивергенцию, чем другие изоляты В группы (Ukraine-Mal-18 имеет 12 аа замен, Ukraine-Ep-18 имеет 25 аа замен, а другие изоляты клады В имеют от 0 до 2 аа замен); ii) имеют аа замены, идентичны непшеничным изолятам группы В1 этого вируса, много аа замен расположены в тех же участках гена СР, что и замены травяных В1 изолятов ВПМП.